Assessment of Soluble PD-1 and PD-L1 in Iraqi Women Patients with Breast Cancer with Toxoplasmosis - Maysoon K. J. Al-Muskakeh; Ali N. Yaseen; Muhammed A. H. Aldabagh (Institute of Medico-legal Publications Pvt Ltd, 2022)
Toxoplasma gondii is an obligate apicomplexan intracellular protozoan parasite and considered the most common global parasite which infects a wide range of warm-blooded animals and is the etiological agent of one of the most common parasitic infections in humans. Breast cancer is the most common cancer in women worldwide; nearly 1.7 million new cases were diagnosed in 2012, making it the second most common type of cancer. The main objective of the present study was to investigate the seroprevalence of the anti-Toxoplasma gondii IgG antibodies in Iraqi breast cancer patients and to clarify the role of soluble programmed death-1 (sPD-1) and (sPD-L1) in Iraqi Iraqi breast cancer patients with toxoplasmosis. Enzyme Linked Immunosorbent Assay (ELISA) was used to detect anti- T. gondii IgG antibodies in the sera of 108 patients with breast cancer and 50 apparently healthy controls. The results showed that 26(26%) samples of sera patients have been founded breast cancer with toxoplasmosis, 80(74%) samples have breast cancer, 10(20%) cases have control toxoplasmosis (those patients were had toxoplasmosis but showing no symptoms) and 40 (80%) cases samples were considered as a control group without any infections. Sera (sPD-1 and sPDL-1) levels were determined by ELISA using a quantitative sandwich enzyme immunoassay technique. The results showed that levels of sPD-1 and sPDL-1 levels were significantly higher in patients group than healthy subjects (P<0.01).